Cross-coupling reactions of aryldiazonium salts with allylsilanes under merged gold/visible-light photoredox catalysis - Akram, Manjur O.; Mali, Pramod S.; Patil, Nitin T. (Organic Letters, 2017)
A method for the cross-coupling reactions of aryldiazonium salts with trialkylallylsilanes via merged gold/photoredox catalysis is described. The reaction is proposed to proceed through a photoredox-promoted generation of an electrophilic arylgold(III) intermediate that undergoes transmetalation with allyltrimethylsilane to form allylarenes.